Micrografting technique in cinchona (Cinchona ledgeriana Moens) plants propagation - Salwa Lubnan Dalimoenthe (Research Institute for Tea and Cinchona, 2013)
In Indonesia has been found 11 cinchona species but only two species recognized as an economically important Cinchona succirubra known as resistant plant to root disease while Cinchona ledgeriana quinine high content. To put together those two characters from mostly through grafting it took twelve months. Micrografting is one of the propagation techniques through tissue culture. Micrografting has already been used in wide spread for plants propagation either only for research or as mass product. Hopefully, the use of micrografting to obtain cinchona propagation would be short more or less 10 months and provide plants as mass production economically. The result showed that micro grafting at V shape could be used as the propagation method on cinchona species besides bud multiplication through tissue culture. MS medium is the best medium for cinchona micrografting. If there is no IBA on rooting media, there is no root formation from the plants. The increasing of IBA from 1 up to 4 mg/l in media, will increase also the number of rooting plants.different plant material as scion and stock and different concentrarions (0,1,2,3,4 mg/l) of IBA gives the significantly different respons on rooting formation. The increasing of IBA on media will increase the number of rooting plants also. The highest rooting formation are found on medium with 3 dan 4 mg/L IBA. The combination between C. ledgeriana-C. succirubra, C. ledgeriana-C.ledgeriana, C. succrirubra-C.succirubra gives significantly difference on the growth dan development of root. The use of C. ledgeriana as a root stock doesn’t showed good rooting formation. The combination between CSA/QRC205 gives the highest number of leaves result compare wth others combination on as much as 9,8. The first stage of acclimatization on culture room with temperature 25-270C and followed by acclimatization on plastics house covered with paranet 70%. In general in vitro planlet cinchona from micrografting growing well. By the end of observation (8 weeks) growing percentage reach 90%.